Analysis of Computational Thinking Ability of High School Students in Solving Statistics problems - Swasto, Widya; Suanto, Elfis; Saragih, Sehatta (Universitas Suryakancana, 2024)
This research is motivated by the importance of computational thinking skills in 21st century learning. This research aims to describe the computational thinking skills of high school students in solving problems on statistics material. This research is a descriptive research with qualitative approach. The subject of the research was class X students of SMA Negeri 7 Pekanbaru, Pekanbaru City as many as 25 students. The data collection technique was done by test and interview. The analysis of students' computational thinking ability is seen through the indicators of computational thinking. The results of the analysis showed that high ability students on decomposition indicators (95.83%) were in the excellent category, on pattern recognition indicators (79.17%) abstraction (79.17%) were in the good category, and on algorithm thinking indicators (66.67%) were in the sufficient category. Medium ability students on decomposition indicators (72.22%) and pattern recognition (63.89%) are in the good category, on abstraction indicators (58.33%) in the sufficient category, and on algorithm thinking indicators (33.33%) are in the low category. Low ability students in the decomposition indicator (55%) are in the sufficient category, low category for the pattern recognition indicator (22.5%) and very low category for the abstraction indicator (17.5%) and thinking algorithm (7.5%).